Our Stories, Our Planet: Imagining a Sustainable and Equitable Planet Through Inclusive Representation and Diverse Narratives - Lee, Sean (Tufts Archival Research Center, 2020)
This thesis project illustrates the need for more identity representation and narrative diversity in the environmental stories we tell to engage everyone.